CPT113/CPM213 – Programming Methodology & Data Structures - February 2022 - PPSKOM, Pusat Pengajian Sains Komputer (2022)
First Semester Examination 2021/2022 Academic Session February 2022 CPT113/CPM213 – Programming Methodology & Data Structures (Metodologi Pengaturcaraan & Struktur Data)